2017
DOI: 10.1556/1646.9.2017.34
|View full text |Cite
|
Sign up to set email alerts
|

The effect of moderate endurance training on gastrocnemius retinol-binding protein 4 and insulin resistance in streptozotocin-induced diabetic rats

Abstract: BackgroundRetinol-binding protein 4 (RBP4) is suggested to be involved in the occurrence of insulin resistance. There are contradictory studies about the effects of exercise training on RBP4 levels and insulin resistance. Hence, we designed this study to investigate the impact of moderate endurance training on gastrocnemius RBP4 and insulin resistance in streptozotocin (STZ)-induced diabetic rats.MethodForty male albino Wistar rats were randomly divided into four groups: healthy control (HC), diabetic control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Additionally, the results of this study showed up regulation of RBP4 expression in HFD rats. From previous hypothesis RBP4 elevates gluconeogenesis in the liver, so hyperglycemia is occurring (Hutchison, Harrison, Stepto, Meyer, & Teede, ), hinders the insulin signaling in muscle and decreases the uptake of glucose by reduction the action of PI3K (Yousefi & TaheriChadorneshin, ). Defects in PI3K reported in other findings (Jiang & Zhang, ).…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, the results of this study showed up regulation of RBP4 expression in HFD rats. From previous hypothesis RBP4 elevates gluconeogenesis in the liver, so hyperglycemia is occurring (Hutchison, Harrison, Stepto, Meyer, & Teede, ), hinders the insulin signaling in muscle and decreases the uptake of glucose by reduction the action of PI3K (Yousefi & TaheriChadorneshin, ). Defects in PI3K reported in other findings (Jiang & Zhang, ).…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, results of current study showed up regulation of RBP4 expression in HFD rats. From previous studies RBP4 i: elevates the process of gluconeogenesis in liver so hyperglycemia is occurred [29], ii: hindered the insulin signaling in muscle and iii: decreased the uptake of glucose by reduction the activity of PI3K [30]. Defects in PI3K demonstrated in other findings [31].…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, RBP4 serves a key role in IR-mediated activation of the JAK2/STAT5 signaling pathway ( 42 , 51 ). RBP4 also participates in development of hyperglycemia in muscle via inhibition of PI3K activity ( 19 , 33 , 54 , 55 ) and in liver via increased PEPCK activity ( 33 , 42 ). It also regulates OS via mitochondrial dysfunction ( 72 , 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the skeletal muscle of Wistar rats, RBP4 levels decrease insulin-dependent glucose uptake ( 54 ). RBP4 is associated with impaired insulin signaling, decreased affinity of insulin receptor substrate (IRS) 1 for PI3K and decreased GLUT4 translocation to the cell membrane, which decreases glucose uptake and increases IR in the muscle ( Fig.…”
Section: Rbp4 In Irmentioning
confidence: 99%